Education and Training Guidelines for the Board of the Korean Society of Gastrointestinal Endoscopy - Hee Seok Moon; Eun Kwang Choi; Ji Hyun Seo; Jeong Seop Moon; Ho June Song; Kyoung Oh Kim; Jong Jin Hyun; Sung Kwan Shin; Beom Jae Lee; Sang Heon Lee (Clinical Endoscopy, 2017)
The Korean Society of Gastrointestinal Endoscopy (KSGE) developed a gastrointestinal (GI) endoscopy board in 1995 and related regulations. Although the KSGE has acquired many specialists since then, the education and training aims and guidelines were insufficient. During GI fellowship training, obtaining sufficient exposure to some types of endoscopic procedures is difficult. Fellows should acquire endoscopic skills through supervised endoscopic procedures during GI fellowship training. Thus, the KSGE requires training guidelines for fellowships that allow fellows to perform independent endoscopic procedures without supervision. This document is intended to provide principles that the Committee of Education and Training of the KSGE can use to develop practical guidelines for granting privileges to perform accurate GI endoscopy safely. The KSGE will improve the quality of GI endoscopy by providing guidelines for fellowships and supervisors.